Diversity of Soil Arthropods in Suranadi Nature Park, Lombok, and its role on science lesson in elementary and secondary school - Mohammad Liwa Ilhamdi; Muhammad Syazali (Jurnal Biologi Tropis, 2021)
The absence of data related to Arthropoda classes other than the orders Lepidoptera and Odonata in Suranadi Nature Park raises the need for studies on these fauna. This study aims to analyze the soil arthropod community and its role in science lessons in primary and secondary schools. This descriptive research was carried out from May to December 2019. Samples were collected in three paths, namely the forest edge, the middle of the forest and the waterway using the pit fall trap method. The collected samples were identified to species taxon at the Biology Laboratory of the Faculty of Teacher Training and Education, Mataram University. To obtain data on species diversity, an analysis was carried out using the Shannon-Wiener equation. There are 33 species of soil arthropods found. They consist of 3 species from the order Blattodea, 2 species from the order Orthoptera, 4 species from Araneae, 11 species from the order Coleoptera, 10 species from the order Hymenoptera, 1 species each from the orders Homoptera, Tysanura and Diptera. The most abundant species is Platidema sp of the order Coleoptera. Based on the results of the analysis, the diversity index of soil Arthtopoda species in Suranadi Nature Park is 2,628. The qualitative analysis shows that there are 2 elementary and junior high school science topics that are suitable to be taught using the concept of soil arthropod diversity at Suranadi Nature Park.